Analysis Of The Effect Of Company Characteristics And Financial Ratios On Debt Policy In Food And Beverages Companies - Lumbanraja, Thorman; Firmansyah, Arie; Yulia, Emi; Rachmat S, R. Achmad; Jaya, Rahmat (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The objective of the study was to empirically test the effect of growth, tangibility, firm size, business risk, liquidity, profitability, corporate tax rate and non-debt tax shield on debt policy in the food and beverage sector companies listed on the Indonesia Stock Exchange over the period from 2005 to 2013. Previous research on this topic was reviewed in order to provide context for the current study. Purposive sampling was utilized as a sampling technique, and seven companies were selected based on predefined criteria. Panel data regression with a fixed effect model was applied to analyze the data, with the objective of testing the hypothesis. The findings indicated that growth, tangibility, firm size, liquidity, profitability, and non-debt tax shield were significant determinants of debt policy. In contrast, business risk and corporate tax rate were found to exert a limited influence on debt policy.